2014
DOI: 10.1038/bjc.2014.251
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression through constitutively activated NF-κB signalling in human ovarian cancer and its reversal by an NF-κB inhibitor

Abstract: Background:Although T-cell immunity is thought to be involved in the prognosis of epithelial ovarian cancer (EOC) patients, immunosuppressive conditions hamper antitumour immune responses. Thus, their mechanisms and overcoming strategies need to be investigated.Methods:The role of NF-κB in human EOC cells and macrophages was evaluated by in vitro production of immunosuppressive IL-6 and IL-8 by EOC cells and in vivo analysis of immune responses in nude mice implanted with human EOC cells using an NF-κB inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 42 publications
(53 reference statements)
2
47
1
1
Order By: Relevance
“…However, our results certainly confirm previous findings: decrease of IL-10 after cytoreduction 16 and an increase of IL-10, TGF-b and arginase in ovarian cancer patients at diagnosis. 17,18 In contrast to reported findings on VEGF, we could not correlate the presence of VEGF to prognosis nor did we see an increase after surgery. [19][20][21][22][23] We found that gal-1 serum levels increased after three cycles of paclitaxel-carboplatin.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results certainly confirm previous findings: decrease of IL-10 after cytoreduction 16 and an increase of IL-10, TGF-b and arginase in ovarian cancer patients at diagnosis. 17,18 In contrast to reported findings on VEGF, we could not correlate the presence of VEGF to prognosis nor did we see an increase after surgery. [19][20][21][22][23] We found that gal-1 serum levels increased after three cycles of paclitaxel-carboplatin.…”
Section: Discussioncontrasting
confidence: 99%
“…Table 1 Arginase-1 MDSC are a heterogeneous group of cells that act immune suppressive and tumor promoting through secretion of inflammatory mediators, such as ROS and NO, IDO and arginase. 8 Arginase-1 causes depletion of L-arginine, which results in T cell anergy 40 Also TAM produce arginase-1 [41][42][43] Increased plasma arginase has been observed in EOC patients 18 …”
Section: Introductionmentioning
confidence: 99%
“…One strategy to reduce the effects of these immunosuppressive cancer stromal cells is to use neutralizing antibodies or inhibitors of immunosuppressive effector molecules produced by the stromal cells. We and other groups previously reported that targeting signaling pathways such as STAT3 or NF‐κB in cancer‐associated immunosuppressive cells could augment anti‐tumor T‐cell immune responses by reducing cancer‐associated immunosuppression . Several studies have shown that currently used molecular target drugs for these pathways have synergistic anti‐tumor effects when combined with immunotherapies through immune‐related mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…Two types of immunosuppression mechanisms operate in the TME 53,54) . One is tumor- Wnt-β-catenin signaling pathway 55,56) , the MAPK signaling pathway 57,58) , the JAK-STAT3 signaling pathway 57,59) , and the NF-κB signaling pathway 60) . .…”
Section: Immunosuppressive Tme and Act Therapiesmentioning
confidence: 99%